Mechanism of gut microbiota and Axl/SOCS3 in experimental autoimmune encephalomyelitis. Issue 7 (2nd July 2019) - Li, Xiao-Ling; Zhang, Bo; Sun, Meng-Jiao; Bao, Cai-Cai; Yuan, Bo-Yao; Xie, Qin-Fang; Wang, Li-Juan; Wang, Man-Xia
Abstract : Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system (CNS). The present study explored the role of intestinal microbiota in the initiation and propagation of mice induced by experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. 48 C57BL/6 were randomly divided into control group and EAE group. The changes of body weight and the scores of neurological function were recorded. The mRNA expression of the receptor tyrosine kinase subfamily (AXL) was detected by real-time quantitative PCR. The levels of IL-17 and IFN-γ in blood samples were examined by ELISA. The intestinal microbial composition of mice at different time points during the EAE induction was analyzed by 16S rRNA gene-based sequencing. In EAE group, the body weight began to reduce at day 3 and neurological symptoms began to appear at day 7 after EAE induction. The levels of IL-17 and IFN-γ in EAE group reached the peak at day 21 and then decreased gradually. However, the expression of Axl and SOCS3 reached the lowest level at day 21 and then increased gradually. The microbiome analyses revealed that the abundances of Alistipes, Blautia, and Lachnospiraceae _NK4A136_group were significantly changed at day 14, whereas the abundances of Allobaculum, Eubacterium and Helicobacter were significantly changed at day 30 of EAE induction. The prevotellaceae_NK3B31_group may be key bacteria that contribute to the development of MS. Regulation of intestinal microbiota composition can become a new therapeutic target for the treatment of MS.